Cosmetic Rhinoseptoplasty in Acute Nasal Bone Fracture. Issue 2 (6th May 2013) - Kim, Ji Heui; Lee, Jung Woo; Park, Chan Hum
Abstract : Objective: Traditionally, rhinoseptoplasty for nasal bone fracture is only considered after an unsatisfactory outcome from initial closed reduction. However, better surgical outcomes may be achieved if rhinoseptoplasty is performed at the same time as the nasal bone fracture reduction. This study investigated the surgical outcomes of patients who underwent rhinoseptoplasty concomitantly with nasal bone fracture reduction according to their computed tomography image‐based nasal bone fracture classifications. Study Design: Case series with chart review. Setting: Academic tertiary care medical center. Subjects and Methods: Fifty‐six patients who underwent rhinoseptoplasty concomitantly with nasal bone fracture reduction were enrolled in this study. Nasal bone fractures were classified into 6 types by computed tomography scans. Two independent facial plastic surgeons evaluated the outcomes 6 months postoperatively using a visual analog scale. The nasal tip projection and rotation were measured using the pre‐ and postoperative profile views. Results: The satisfaction scores of type I, IIo, and IIIo fractures without septal fracture were significantly higher than those of type II, III, and IV fractures with septal fractures. Among the patients, 82.1% underwent lower vault surgery. The nasal tip projection and rotation were increased after surgery in patients without septal fractures, whereas the tip rotation was elevated but the projection was unchanged postoperatively in patients with septal fractures. Conclusion: Rhinoseptoplasty for acute nasal bone fractures can be performed at the same time as nasal bone fracture reduction. However, nasal bone fracture with septal fracture should be managed carefully.